El criterio de responsabilidad social en el Sistema Nacional de Contratación Pública y su impacto en el gasto público institucional - Acero Catucuago, Mayte Sherillyn (2024)
The criterion of social responsibility in Ecuadorian public procurement is a principle that goes beyond mere legal compliance to include actions that contribute to the welfare and sustainability of society. This criterion is analyzed in the context of efficiency and transparency in public management, considering its impact on institutional spending. The research highlights how the application of this principle can improve efficiency in the administration of public resources, in line with the constitutional foundations established in Article 288 of the Constitution of the Republic of Ecuador. The general objective is to analyze, through a legal doctrinal study, the criterion of social responsibility in the national public procurement system to determine its effect on institutional spending, using the GADM-Riobamba as a case study. Methodologically, the research adopts a qualitative approach, using legal-doctrinal, legal-descriptive, and case study methods. It is exploratory, legal-doctrinal, legal-descriptive research with a non-experimental design, using research techniques such as interviews to examine the configuration and impact of this criterion in public procurement and institutional spending. Finally, it highlights the challenges in the practical implementation of this criterion, such as deficiencies in planning and control that result in inefficient use of resources. The research underscores the need to strengthen training, citizen participation, and project management mechanisms to optimize public spending and improve the effectiveness of government contracting.